The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1109/2944.991411
|View full text |Cite
|
Sign up to set email alerts
|

Optical MEMS devices based on moving waveguides

Abstract: The paper deals with optical microelectromechanical systems (MEMS), and in particular with optical MEMS based on moving waveguides. After a short overview of this very attractive novel activity, specific technological problems and solutions are discussed. Then the following examples of recent developments based on silica on silicon technology are presented: optical switch, vibration sensor, and optical scanner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
68
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(68 citation statements)
references
References 16 publications
(18 reference statements)
0
68
0
Order By: Relevance
“…Also it is important to note that the criteria for detector lifetime degradation is based on receiving an unacceptable signal to noise ratio (SNR) output as a result of the accelerated temperature life test. There has been much interest in optoelectronic integrated devices (OEIDs) [2,5,9]. which are important for optical information processing and optical computing.…”
Section: Led Device Mo Deling Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Also it is important to note that the criteria for detector lifetime degradation is based on receiving an unacceptable signal to noise ratio (SNR) output as a result of the accelerated temperature life test. There has been much interest in optoelectronic integrated devices (OEIDs) [2,5,9]. which are important for optical information processing and optical computing.…”
Section: Led Device Mo Deling Analysismentioning
confidence: 99%
“…Such conditions are frequently encountered in many system applications, as well as in optocouplers (which contain LEDs). Another important factor is degradation during normal operation (wearout) which causes gradual decrease in light output [9]. Wearout degradation produces changes in LED characteristics that have many similarities to displacement damage.…”
Section: Introductionmentioning
confidence: 99%
“…MOEM devices using a single cantilever have been demonstrated previously, for example, where a moveable waveguide is displaced relative to a fixed waveguide. Ollier et al fabricated an optical switch based on silica-on-silicon technology that used electrostatic switching to function as a switch between channel waveguides [2]. While single cantilevers provide a way to create devices, the use of dual cantilevers has been pioneered by Park et al as a way of attracting cells to adhere to a cantilever, whereon they can be cultured and weighed using a resonance frequency method [3].…”
Section: Introductionmentioning
confidence: 99%
“…1,5 Recently, it was shown that motion of micron-scale devices can be monitored through changes in end-to-end alignment of optical waveguides. [9][10][11] In this letter, we propose an integrated and near-field optical motion detection technique that exploits near-field optical evanescent-wave coupling. We demonstrate that the technique works efficiently for nanoscale mechanical resonators, with greater sensitivity than conventional optical techniques.…”
mentioning
confidence: 99%